Cine MRI of the Triangular Fibrocartilage Complex during Radial–Ulnar Deviation - Nakamura, Toshiyasu; Abe, Koji; Terada, Nobuki (Journal of Wrist Surgery, 2018)
Purpose Changes in the shape of the triangular fibrocartilage complex (TFCC) during radial–ulnar deviation were studied using “cine-mode” magnetic resonance imaging (MRI) in 10 right wrists of healthy volunteers, 5 wrists of TFCC tear, and 5 wrists of ulnar styloid nonunion.Subjects and Methods The wrist was fixed in a custom acrylic device, which only allows radial and ulnar deviation. Coronal MR images of nine radial–ulnar deviated positions (every 5 degree from 15 degrees radial deviation to 25 degrees ulnar deviation) were obtained in volunteers and patients. Cine-mode MRI was assembled and was output to MPEG video to observe.Results Cine MRI demonstrated the ulnar side of the TFCC was elongated by average 15 mm in 15 degrees of radial deviation and shortened by average 8 mm in 25 degrees of ulnar deviation in all normal TFCC subjects. Distal portion of the triangular fibrocartilage (TFC) was compressed during radial–ulnar deviation in 10 healthy volunteers and in 3 patients, but proximal portion of the TFC was stable throughout the motion. In contrast, the wavy deformities on the disc in ulnar deviation were observed in three patients with horizontal tear inside the TFCC. In nonunion of the ulnar styloid process, the fragment was snapped in maximum ulnar deviated position or elongation of the space between the styloid fragment and ulna was seen.Conclusion This study indicated normal and abnormal changes in the shape of the TFCC during radial–ulnar deviation motion on cine MRI. The abnormal dynamic changes of the TFCC may be seen in ulnar deviated position in patients, which are related to positive ulnocarpal stress test with the wrist forced ulnar deviated.
Keywords: cine-mode MRI; triangular fibrocartilage complex; radioulnar deviation; changes in shape